Audio Interaction in Computer Mediated Games. (13th November 2007) - Parker, J. R.; Heerema, John
Abstract : The use of sound in an interactive media environment has not been advanced, as a technology, as far as graphics or artificial intelligence. This discussion will explore the use of sound as a way to influence the player of a computer game, will show ways that a game can use sound as input, and will describe ways that the player can influence sound in a game. The role of sound in computer games will be explored some practical design ideas that can be used to improve the current state of the art will be given.